Pengembangan Aplikasi PILARIYYAH untuk Membantu Memudahkan Siswa SD dalam Mempelajari Huruf Hijaiyyah dan Makharijul Huruf - Wildan Pratama Hariansyah; Seli Aliani; Al Qomariah; Ani Nur Aeni (Journal on Education, 2023)
This research aims to develop the Pilariyyah application to assist elementary school students in learning the Hijaiyyah and Makhraj letters using the D&D research method. The application is designed to facilitate elementary school students in learning the Hijaiyyah and Makhraj letters more effectively. The study uses a D&D approach, including needs analysis, design, development, testing, and evaluation. Data is collected through interviews, observations, and questionnaires. After the development stage, the Pilariyyah application was tested on 28 elementary school students as research subjects. The results of the study show that the Pilariyyah application successfully helped elementary school students learn the Hijaiyyah and Makhraj letters. The application can increase students' interest and motivation in learning and provide a more interesting and interactive learning experience. Additionally, the application provides an easier way of learning because it can be accessed anytime and anywhere using mobile devices. Overall, the development of the Pilariyyah application is a significant contribution in the field of education, especially in teaching the Hijaiyyah and Makhraj letters to elementary school students. With the increasing use of technology in education, this application provides an innovative and effective way of learning for students. The design and development of the application were based on the needs and requirements of the target audience. The use of interactive features such as audio-visuals in the application makes learning more interesting and motivates students to learn.